Development of Literary Critical Debate Genre - Sh.N.Akhmedova; M.Khudoykulova (International Journal on Human-Computing Studies, 2021)
The article discusses the peculiarities and development of the genre of debate in the genre system of Uzbek criticism. The genesis of the debate goes back to folklore and classical literature, the development of the 20-30s of the twentieth century. At the same time, the role of the debate genre in the literary process, in the development of literature is defined.